Relationship of Crime to Crisis and Disaster Management in the Kingdom of Saudi Arabia - ALZHRANI, AHMAD ABDULLAH (Journal of Risk and Crisis Management, 2019)
Objectives of the study:• Know the causes of crimes at the time of disasters and crises.• Identify the role that crisis and disaster management should play in confronting crimes.• Know the implications of committing crimes during disasters and crises.• Identify the stages of preparing preparedness plans in different areas where disasters and crises occur and how to increase the effectiveness of these plans to combat crimes. The study used the descriptive approach to suit its nature and achieve its objectives. The tool was represented in a questionnaire that was applied to a random sample of (100) individuals.Results: That crises and disasters represent a very fertile environment for the commission of crimes of various kinds and forms, especially in the event of security personnel to save the lives of citizens and residents and the provision of vital facilities, so must activate the role of civil society institutions in addition to the private sector in securing the property and life of citizens.Recommendations:• Prepare the scenario corresponding to the reality of previous crimes and develop a number of solutions to deal with.• Training security personnel on how to manage the crisis and how to control the course of the crisis or disaster.• The work of awareness seminars on the seriousness of the times of crises and disasters and it is necessary to control the stages of the crisis.
Keywords: Crime; Crisis and Disaster Management; Saudi Arabia